Pengaruh Strategi Promosi, Kualitas Produk dan Kepuasan Pelanggan Terhadap Keputusan Pembelian Aksesoris Hijab Pada Penjualan Online Bericcy’s Shop - Cut Putri Dwita (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2024)
The problem in this research is the dropping of promotion strategy, product quality and customer satisfaction to purchase decision of hijab accessories at Bericcy's Shop online. The purpose of this research is to analyze the influence of promotion strategy, product quality and customer satisfaction to purchase decision of hijab Accessories at online sale of Bericcy's Shop. The number of samples of this study were 72 customers. The data were collected through questionnaires. Hypothesis testing using multiple linear regression analysis, F test (simultaneous) and t test (partial) is intended to know in a way san partially influence independent variables dependent on dependent variable at 95% confidence level (α = 0,05). The results of research based on simultaneous test show that between variable Promotion Strategy, Product Quality and Customer Satisfaction have a significant effect to Decision of Purchasing Hijab Accessories on Bericcy's Shop Online Sales. While only partially variable Promotion Strategy and Customer Satisfaction have a significant effect on the Decision of Purchasing Hijab Accessories at Bericcy's Shop Online Sales. While the product quality variable does not affect the Decision of Purchasing Hijab Accessories on Bericcy's Shop Online Sales.